Hydrogel Dressing Containing Basic Fibroblast Growth Factor Accelerating Chronic Wound Healing in Aged Mouse Model - Yonghao Xiao; Hui Zhao; Xiaoyu Ma; Zongheng Gu; Xin Wu; Liang Zhao; Lin Ye; Zengguo Feng (Molecules, 2022)
Due to the decreasing self-repairing ability, elder people are easier to form chronic wounds and suffer from slow and difficult wound healing. It is desirable to develop a novel wound dressing that can accelerate chronic wound healing in elderly subjects to decrease the pain of patients and save medical resources. In this work, Heparin and basic fibroblast growth factor(bFGF) were dissolved in the mixing solution of 4-arm acrylated polyethylene glycol and dithiothreitol to form hydrogel dressing in vitro at room temperature without any catalysts, which is convenient and easy to handle in clinic application. In vitro re-lease test shows the bFGF could be continuously released for at least 7 days, whereas the dressing surface integrity maintained for 3 days degradation in PBS solution. Three groups of treatments including bFGF-Gel, bFGF-Sol and control without any treatment were applied on the full-thickness wound on the 22 months old mice back. The wound closure rate and histological and immunohistochemical staining all illustrated that bFGF-Gel displayed a better wound healing effect than the other two groups. Thus, as-prepared hydrogel dressing seems supe-rior to current clinical treatment and more effective in elderly subjects, which shows promising potential to be applied in the clinic.